1991
DOI: 10.1103/physreva.44.1931
|View full text |Cite
|
Sign up to set email alerts
|

Three-level atoms in phase-sensitive broadband correlated reservoirs

Abstract: A three-level atom with two competing transitions can sense correlations between modes of an electromagnetic field with which it interacts. We examine the sensitivity of three-level atoms in ladder, A, and V configurations to correlations between modes in a broadband correlated reservoir of field modes. Our model of a correlated reservoir includes pairwise mode correlations around a center frequency.When such correlations are set to zero, the reservoir becomes a simple thermal heat bath, but in the opposite ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 63 publications
(50 reference statements)
0
23
0
Order By: Relevance
“…The two-mode squeezed vacuum [8], where the squeezing operator is given by the more generalised form…”
Section: Resultsmentioning
confidence: 99%
“…The two-mode squeezed vacuum [8], where the squeezing operator is given by the more generalised form…”
Section: Resultsmentioning
confidence: 99%
“…Note that the squeezing parameters M and N are slowly varying functions of the frequency and characterize the SV field, such that jMj 2 NðN þ 1Þ, the equality sign describes the squeezing is pure. 28) And the relative phase È ¼ 2 À ' denotes the phase difference between the coherent field and the SV field, where is the phase of coherent field. In this paper, we just consider a ideal squeezed state, i.e., jMj 2 ¼ NðN þ 1Þ.…”
Section: Model and Equationsmentioning
confidence: 99%
“…21) They also showed that the atomic system becomes sensitive to the amplitude and the phase of the SV field, and a notable influence on the refraction index was induced by the squeezed field. 22) Besides, much attention, such as twophoton transition, [23][24][25][26] the steady-state populations, [27][28][29] and the resonance fluorescence, [30][31][32][33] was paid to the effects of the SV on a three-level atom in^, _ and ladder schemes.…”
Section: Introductionmentioning
confidence: 99%
“…In a threelevel atom in lambda, vee and ladder configurations interacting with a squeezed vacuum field, there are spectacular qualitative changes in the steady-state populations relative to the ordinary vacuum, including two-photon population inversion [10][11][12]. Futher work has also been done to study the effect of a broad-band squeezed vacuum on the resonance fluorescence from three-level atoms [14][15][16].…”
Section: Introductionmentioning
confidence: 97%
“…The effects of a broad-band squeezed vacuum on threelevel atoms have also been investigated [10][11][12][13]. In a threelevel atom in lambda, vee and ladder configurations interacting with a squeezed vacuum field, there are spectacular qualitative changes in the steady-state populations relative to the ordinary vacuum, including two-photon population inversion [10][11][12].…”
Section: Introductionmentioning
confidence: 98%